Developing a model of life satisfaction among Indonesian Muslims who perform hijrah - Juliarni Siregar (2024)
The hijrah movement in Indonesia is growing rapidly due to the influence of popular culture, information technology, and Islamic preaching. This growth has led to the interpretation of hijrah as a trend rather than an act of repentance, making it challenging for those performing hijrah to achieve life satisfaction. This research investigates factors influencing life satisfaction among hijrah performers in Indonesia. It focuses on five independent variables: religious struggle, religious coping, religious practices, religious transformation, and personality traits, along with two mediator variables: religious support and attachment to God. The study involved 475 Muslims performing hijrah on the islands of Java and Sumatra, obtained through snowball sampling. The results of the model test conducted using Structural Equation Model (SEM) analysis showed the following: (1) religious struggle and religious transformation indirectly affect life satisfaction through religious support, (2) religious practices indirectly affect life satisfaction through attachment to God and religious support, and (3) religious coping and personality have a direct effect on life satisfaction. The R2 value revealed that the variation in attachment to God explained by religious practices is 11.3%. The variation in religious support explained by religious struggle, religious transformation, and attachment to God is 23.8%. Finally, the variation in life satisfaction explained by religious coping, religious support, and personality is 18.9%. Generally, it can be inferred that the life satisfaction model is satisfactory. The findings of this research have significant implications for the advancement of life satisfaction theory, which employs Islamic psychology and psychotherapy to purify the soul through Islamic worship. Additionally, it is crucial to enhance religious support within the hijrah community, as this can assist Muslims who perform hijrah in achieving life satisfaction.